Studying of Crimean Hemorrhagic Fever Natural Focality in the Republic of Ingushetia - A.A. Kartoev; N.F. Vasilenko; O.V. Maletskaya; N.G. Varfolomeeva; T.N. Orlova; G.K. Ismailova; M.P. Grigor`eva; B.D. Komurzoev; A.N. Kulichenko (Проблемы особо опасных инфекций, 2009)
Presented are the results of epizootiological and epidemiological monitoring of Crimean hemorrhagic fever (CHF) in the territory of the Republic of Ingushetia. 6 cases of CHF were registered and confirmed during 5 years (2004-2008), 3 (50 %) of them being fatal. 5 species of ixodic ticks were shown to be infected with Crimean hemorrhagic fever virus of which 67,7 % were ticks Boophilus annulatus. CHF virus antigen and specific antibodies were detected in great and small cattle. Specific antibodies in titres 1:800 - 1:1600 were found in blood serum of donors. Data received confirmed the presence of CHF natural focus in the territory of the Republic of Ingushetia.